VARIASI KETEBALAN LIMBAH KULIT UBI KAYU DAN KULIT DURIAN UNTUK MENURUNKAN KADAR BESI (Fe) DAN MANGAN (Mn) DALAM AIR SUMUR GALI - Arifin, Zainal; Reflis, Reflis; Putra Utama, Satria; Mustopa, M.; Bertham, Yudhy Harini (Poltekkes Kemenkes Bengkulu, 2022)
This study aims to determine the appropriate thickness of cassava skin and durian skin in reducing the levels of Fe and Mn contained in dug well water. The study was designed using a single factor complete randomized design, namely the thickness of the waste cassava skin and durian skin which included 0 cm (control), 15 cm, 30 cm, and 60 cm. Each treatment was repeated 3 times to obtain 12 experimental units. Water samples were taken by a dug well from one of the residents' houses in RT 08, Padang Serai Village, Bengkulu City. Furthermore, the water samples were taken to the Bengkulu Ministry of Health Poltekkes Environmental Health Workshop. Observational data will be analyzed statistically using ANOVA level of 5%. Then if the data is significantly different, it will be tested further with the Least Significant Difference (LSD) Test. The results showed that the application of cassava peels and durian peels reduced Fe and Mn levels compared to controls. Application of cassava skin waste and durian skin with a thickness of 30 cm in water treatment of dug wells because they are able to reduce Fe and Mn levels below the threshold and is more economical.